2016
DOI: 10.1016/s1875-5364(16)60002-x
|View full text |Cite
|
Sign up to set email alerts
|

Bitter melon: a panacea for inflammation and cancer

Abstract: Nature is a rich source of medicinal plants and their products that are useful for treatment of various diseases and disorders. Momordica charantia, commonly known as bitter melon or bitter gourd, is one of such plants known for its biological activities used in traditional system of medicines. This plant is cultivated in all over the world, including tropical areas of Asia, Amazon, east Africa, and the Caribbean and used as a vegetable as well as folk medicine. All parts of the plant, including the fruit, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
133
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 119 publications
1
133
0
6
Order By: Relevance
“…charantia is known to inhibit the growth of cancer cells by inducing of apoptosis (Dandawate et al, 2016). For example, the protein MAP30 present in São Caetano melon seeds, has an effect on liver cancer, HepG2 hepatocellular carcinoma models of human hepatoma and rat cells .…”
Section: Anticancer Effectmentioning
confidence: 99%
“…charantia is known to inhibit the growth of cancer cells by inducing of apoptosis (Dandawate et al, 2016). For example, the protein MAP30 present in São Caetano melon seeds, has an effect on liver cancer, HepG2 hepatocellular carcinoma models of human hepatoma and rat cells .…”
Section: Anticancer Effectmentioning
confidence: 99%
“…Previous studies indicated that MAP30 exhibits a variety of anti-infection, anti-diabetic, antiviral and antitumor bioactive effects (4)(5)(6)(7)(8)(9)(10). The antitumor ability of MAP30 has been the subject of previous studies (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The fruits of the wild variety are of one-fifth comparing to the cultivated analogue. Karela has been used worldwide for a number of ailments, including diabetes, hypertension, obesity, cancer, as well as AIDS, and hundreds of studies have been published regarding these biological activities (Dandawate et al, 2016;Fang and Ng, 2011;Habicht et al, 2014;Tan et al, 2016;Upadhyay et al, 2015). The biological activity is usually attributed to the content of triterpenoids and proteins, for example momordicines, cucurbitacins and momorcharins (Grover and Yadav, 2004).…”
Section: Introductionmentioning
confidence: 99%